Postural Activity During Use of a Head-Mounted Display: Sex Differences in the “Driver–Passenger” Effect - Curry, Christopher; Peterson, Nicolette; Li, Ruixuan; Stoffregen, Thomas A. (Frontiers in Virtual Reality, 2020)
Motion sickness is common in virtual environments. The risk of motion sickness varies widely between individuals, and across situations. The subjective experience of motion sickness often is preceded by distinctive patterns of movement in the control of head and body posture. Previous research has documented reliable sex differences in the kinematics of postural activity, as well as reliable differences in postural activity between participants who were in control of a virtual vehicle and participants who were not. We asked whether postural precursors of motion sickness would simultaneously be influenced by individual and situational factors. We analyzed movement of the head and torso while seated participants were exposed to a driving video game presented via a head-mounted display. Half of the participants were women, and half men. Using a yoked control design, half of participants controlled the virtual vehicle (Drivers), while half watched previously recorded vehicle trajectories (Passengers). The maximum exposure duration was 15 minutes, but participants were instructed to discontinue participation immediately if they experienced any symptoms of motion sickness, however mild. We analyzed movement kinematics in terms of sex and vehicle control, but also in terms of participants who did or did not report motion sickness. Movement differed between Drivers and Passengers, both in terms of the spatial magnitude and multifractality of movement. The spatial magnitude of movement was simultaneously influenced by sex (Men vs. Women) and vehicle control (Drivers vs. Passengers). In addition, in statistically significant interactions we identified postural precursors of motion sickness that differed between Drivers and Passengers and, separately, between Drivers and Passengers as a function of sex. The results are consistent with the postural instability theory of motion sickness etiology, and shed new light on the multifactorial origins of postural precursors of motion sickness in virtual environments